Kidney weight and volume among living donors in Brazil - Vasconcelos, Vladimir Tonello De; Katayama, Rafael Cauê; Ribeiro, Maria Flavia de Lima; Medina-Pestana, José Osmar; Baptista-Silva, José Carlos Costa (São Paulo Medical Journal, 2007)
CONTEXT AND OBJECTIVE: The present study was performed to measure kidney weight and volume among living donors of both sexes in Brazil. DESIGN AND SETTING: This was a cross-sectional survey carried out between December 2001 and August 2004. METHODS: Kidney transplantations from 219 living donors were analyzed for this study. The kidneys were weighed in grams on a singlepan digital balance just after drainage of the perfusion fl uid and removal of the perirenal fat. The kidney volume was determined in milliliters by water displacement. RESULTS: The mean age at nephroureterectomy was 44 ± 9.5. The donor organs came from the left side in 172 cases and from the right side in 47 cases. The weights and volumes of the right and left kidneys were, respectively, 169.83 ± 29.91 g and 157.38 ± 31.84 ml; and 173.00 ± 33.52 g and 160.34 ± 34.40 ml. The differences between the sides were not signifi cant. CONCLUSIONS: According to the present study, kidney weight cannot be the only factor determining the side on which nephroureterectomy is performed, because of the lack of statistical signifi cance between the two sides. On average, females donate lower nephron doses than males do, which could in some transplants result in allograft damage.